Hawaiian black coral (Antipatharia) complete mitochondrial genomes have limited phylogenetic signal for taxonomic resolution of species - Van Wishingrad; Leah E. K. Shizuru; Kenji Takata; Anthony D. Montgomery; Daniel Wagner; Robert J. Toonen (PeerJ)
Most inferences about black coral (Antipatharia) phylogenetics have relied on a handful of molecular markers from PCR-Sanger methods but recently complete mitogenomes are shedding additional light on relationships. We present the most complete survey of shallow-water to mesophotic Hawaiian black corals (‘ēkaha kū moana) to date based on complete mitogenome sequences. The phylogenetic relationships inferred from whole-mitochondrial phylogenies recover Myriopathidae as monophyletic with Myriopathes and Tanacetipathes as the outgroups to all other Hawaiian black coral taxa. Combining our data with other published mitochondrial datasets for black corals, we find that morphologically similar Cirrhipathes cf. anguina specimens are divergent and may not be conspecifics. Likewise, the genera Antipathes and Stichopathes (family Antipathidae) include species that are more divergent from one another than they are to other genera in family Aphanipathidae. Overall, data show Myriopathidae is a monophyletic family, but the families Aphanipathidae and Antipathidae are polyphyletic, and the genera Antipathes and Stichopathes live up to their reputation as a “taxonomic dumping ground”. These phylogenetic analyses underscore the need for continued research to understand the evolutionary history and phylogenetic relationships for black corals generally and ‘ēkaha kū moana specifically.